If the Cops Won’t, Maybe a Gang Will: How Self-Help Explains Procedural Justice as a Predictor of Gang Membership - Geibler, Robert H. (Criminal justice and behavior, 2025)
Procedural justice is linked to several outcomes such as conformity. We examine whether the relationship between procedural justice and gang membership can be explained by how much youth believe gangs can protect them. Using data from the Gang Resistance Education and Training evaluation (G.R.E.A.T. II), we use path analysis to examine the effect of procedural justice on gang membership and the mediating role of the perceived protection of gangs. Our results indicate there is no direct effect of procedural justice on subsequent gang membership, but there are indirect effects through the perceived protection of gangs. These perceptions fully mediate the relationship between procedural justice and gang membership. Youth with lower procedural justice may not believe police can protect them and are more likely to join a gang for protection. As suggested by the literature on self-help, youth look to gangs for personal safety when law enforcement is unavailable.